Ecological Momentary Assessment: A Field Evaluation of Subjective Ratings of Speech in Noise. Issue 6 (November 2021) - Jenstad, Lorienne M.; Singh, Gurjit; Boretzki, Michael; DeLongis, Anita; Fichtl, Elmar; Ho, Rachel; Huen, Myron; Meyer, Vincent; Pang, Flora; Stephenson, Ellen
Abstract : Purpose: As hearing rehabilitation research evolves to include both retrospective and momentary assessment outcome measures, it is important to understand how in-the-moment contextual factors influence subjective ratings. We aimed to determine, over a 4-week period of participants responding to ecological momentary assessments (EMAs) in their own environments, whether: (1) participants will complete surveys in speech-in-noise listening situations; (2) ratings of speech in noise change in a predictable manner as the acoustic conditions change; and (3) EMAs provide patient insights beyond those provided from retrospective ratings. Design: Fourteen adults aged 26 to 86 years with at least 6 months of hearing aid experience were recruited for an 8-week crossover field trial (4 weeks wearing hearing aids with no EMA; 4 weeks wearing hearing aids with EMA). Participants were fitted with hearing aids and provided with a streamer and a smartphone with an app that analyzed the acoustic signal from the hearing aids and alerted the participant to respond to a survey when predetermined acoustic conditions were detected. Participants were prompted to complete brief surveys up to 9 times/day that contained establishing questions, quality ratings, and items assessing perceived benefit, residual activity limitation, and satisfaction. Participants also completed retrospective questionnaires at intake and after each 4-week field trial. Results: Participants completed an average of 4.4 surveys per day. The quality ratings changed as the acoustics changed: Ratings of intelligibility were lower for 10 dB signal-to-noise ratio (SNR) than 20 dB SNR ( p = 0.006); ratings of noisiness were higher for 10 dB SNR than 20 dB SNR ( p = 0.001) and higher for 65 dB SPL than 50 dB SPL ( p < 0.001); ratings of effort were higher for 65 dB SPL than 50 dB SPL ( p = 0.004); ratings of loudness were higher for 65 dB SPL than 50 dB SPL ( p = 0.001). Descriptive analysis of satisfaction, benefit, and residual activity limitation responses showed that the momentary surveys provided more detail about individual variability across acoustic conditions than the retrospective questions. Conclusions: Participants completed more than 99% of the triggered surveys, demonstrating high compliance. Because the quality ratings generally changed in the hypothesized direction, it is concluded that the participants provided valid responses. The greater variability in responses with EMA than retrospective questionnaires demonstrates its potential utility as a clinical tool for exploring hearing aid outcomes in real-world environments. Abstract : Supplemental Digital Content is available in the text.